Address Choice in Dutch 2: Pragmatic Principles of Address Choice in Dutch. (2nd September 2018) - Vismans, Roel
ABSTRACT: This paper reports on research into the use of Dutch forms of address (i.e. the second-person pronouns u and je / jij ) among two generations in the Netherlands. Its main aim is to determine the factors behind different choices of address pronoun. It takes the model of address choice proposed by Clyne et al. in Language and Human Relations (Cambridge University Press, 2009), and more specifically their concept of general pragmatic principles, as its theoretical inspiration. The research is based on a questionnaire in which respondents were asked which pronoun they used to address a variety of interlocutors. The questionnaire also asked respondents to reflect on their choice, especially if it was ambivalent (i.e. if they would address the same type of interlocutor sometimes with u and sometimes with je / jij ). It is the qualitative analysis of these reflections that is the focus of this paper. Although there is some variation between the age groups' evaluation of the importance of some principles, the article establishes (relative) age and familiarity as the leading principles in Dutch address choice. There is also a high level of meta-sociolinguistic awareness of the mechanisms behind address choice. The conclusion suggests a number of modest enhancements to Clyne et al.'s model of address choice.